2005
DOI: 10.1590/s0482-50042005000500004
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da atividade inflamatória e uso de glicocorticóide nas variáveis nutricionais da artrite idiopática juvenil

Abstract: Objetivo: avaliar o estado nutricional na artrite idiopática juvenil (AIJ), a influência da atividade inflamatória e o uso de glicocorticóide. Métodos: foram estudados 116 pacientes com AIJ diagnosticados segundo os critérios da ILAR/1997. Subtipo e atividade da doença foram determinados por reumatologistas pediátricos, e a dose cumulativa de glicocorticóide foi revisada nos prontuários dos pacientes. Foram determinados os percentis do índice de massa corporal (IMC) e da prega cutânea tricipital (PCT) e o esco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
(69 reference statements)
0
3
0
3
Order By: Relevance
“…Já no que diz respeito à AIJ, há uma vasta literatura sobre o déficit de crescimento; no entanto, os estudos que avaliam o consumo alimentar em crianças e adolescentes adotam métodos diferentes [1][2][3][19][20][21][22][23] .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Já no que diz respeito à AIJ, há uma vasta literatura sobre o déficit de crescimento; no entanto, os estudos que avaliam o consumo alimentar em crianças e adolescentes adotam métodos diferentes [1][2][3][19][20][21][22][23] .…”
Section: Discussionunclassified
“…Na fase de atividade das doenças eleva-se a necessidade proteica tendo em vista a proteólise muscular e a elevação da excreção urinária de nitrogênio. Por outro lado, o consumo excessivo de proteínas poderia levar à perda de peso, majoritariamente de massa muscular, pois calorias não proteicas são utilizadas para a incorporação da proteína consumida em excesso [1][2][3]26 .…”
Section: Aij (N = 48) Les (N = 22)unclassified
See 1 more Smart Citation
“…Also in 1999, in preliminary studies, HSCs were transplanted into a patient with systemic sclerosis presenting cutaneous, pulmonary and digestive involvement, who received low-dose conditioning. Transient improvement of intestinal symptoms was observed; however, 3 months after transplantation the patient presented a hypertensive episode and resurgence of the intestinal symptoms, and the immunosuppressive conditioning regimen was repeated [42].…”
Section: Cell Therapy In Rheumatologymentioning
confidence: 98%
“…One Brazilian project started in 2001 primarily used autologous unmanipulated HSCs and in vivo depletion of T cells for the treatment of severe forms of systemic lupus erythematosus and multiple sclerosis refractory to conventional therapy. Forty patients with multiple sclerosis, nine with type I diabetes mellitus, one with amyotrophic lateral sclerosis, two with pemphigus, and 18 patients with rheumatic diseases received HSC transplants [42]. The results obtained for systemic lupus erythematosus showed that eight patients included in the HSC protocol had glomerulonephritis refractory to immunosuppression.…”
Section: Cell Therapy In Rheumatologymentioning
confidence: 99%